Direct evidence of central nervous system axonal damage in patients with postoperative delirium: A preliminary study of pNF-H as a promising serum biomarker. (13th July 2017) - Inoue, Reo; Sumitani, Masahiko; Ogata, Toru; Chikuda, Hirotaka; Matsubara, Takehiro; Kato, So; Shimojo, Nobutake; Uchida, Kanji; Yamada, Yoshitsugu
Highlights: The biomarker, pNF-H, was positive in about two-thirds of postoperative delirium patients. We revealed that delirium can be associated with anatomical damage in the neural system. The neuronal damage of delirium patients was correlated with the clinical manifestations. This suggests the potential of serum pNF-H to serve as an objective biomarker of delirium severity. Abstract: Introduction: Approximately 50–80% patients experience postoperative delirium, an acute cognitive dysfunction associated with prolonged hospitalization, increased mortality, excess healthcare costs, and persistent cognitive impairment. Elucidation of the mechanism of delirium and associated diagnostic and therapeutic measures are urgently required. Here we investigated the role of phosphorylated neurofilament heavy subunit (pNF-H), a major structural protein in axons, as a predictive maker of postoperative delirium. Material and methods: Twenty-three patients who underwent surgery for abdominal cancer were screened for postoperative delirium, and they were assessed for its severity using the memorial delirium assessment scale (MDAS) at and 48 h after delirium onset. Serum pNF-H levels were also measured at both time points. The patients were divided into two groups according to the presence or absence of pNF-H. Clinical variables were compared between groups using the Mann–Whitney U test, and the relationship between pNF-H levels and delirium severity was analyzed using the exponential curve fitting. Results: Fifteen of the 23 (65.2%) patients tested positive for pNF-H, and these patients exhibited significantly higher MDAS scores compared with the pNF-H-negative patients only at the onset of delirium. Although the MDAS score significantly improved over time in the positive group, pNF-H positivity persisted. There was a correlation between the maximum pNF-H level and maximum MDAS score ( R 2 = 0.31, p = 0.013). Conclusions: More severe postoperative delirium was directly related to higher serum pNF-H levels, suggesting the potential application of pNF-H as a quantitative biomarker of neural damage in postoperative delirium.